2018
DOI: 10.1371/journal.pone.0200315
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of FUT8 expression in relation to p53 status in stage II and III colorectal cancer

Abstract: The expression of fucosyltransferase 8, an enzyme responsible for core fucosylation encoded by FUT8, influences tumor biology and correlates with patient prognosis in several solid cancers. We hypothesized that p53 alteration modifies prognostic associations of FUT8 expression in colorectal cancer (CRC), since FUT8 has recently been identified as a direct transcriptional target of wild-type p53. Utilizing multiple datasets of microarray and RNA sequence of CRC, FUT8 mRNA was found to be highly expressed in wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Previous studies have evaluated variety of genetic changes that appear to influence the prognosis of CRC patients, including microsatellite instability (MSI), RAS mutation, BRAF mutation, the human epidermal growth factor receptor 2 gene (HER2) (De Roock et al, 2010;Liu et al, 2017Liu et al, , 2018Noda et al, 2018;Salvia, Lopez-Gomez & Garcia-Carbonero, 2018). HER2 gene, which is located on chromosome 17q21, is a tyrosine kinase receptor and encodes for a 185-kDa transmembrane protein (Salvia, Lopez-Gomez & Garcia-Carbonero, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have evaluated variety of genetic changes that appear to influence the prognosis of CRC patients, including microsatellite instability (MSI), RAS mutation, BRAF mutation, the human epidermal growth factor receptor 2 gene (HER2) (De Roock et al, 2010;Liu et al, 2017Liu et al, , 2018Noda et al, 2018;Salvia, Lopez-Gomez & Garcia-Carbonero, 2018). HER2 gene, which is located on chromosome 17q21, is a tyrosine kinase receptor and encodes for a 185-kDa transmembrane protein (Salvia, Lopez-Gomez & Garcia-Carbonero, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Soreide et al (37) reported that cell cycle and apoptosis are associated with the prognosis of CRC. Numerous studies have reported a relationship between P53 and the development of CRC (3840). However, to the best of our knowledge, the functional correlations of DNA repair, cell cycle, apoptosis and P53 with CXCL3 have not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Known p53-positive cases were used as positive external controls for p53 immunostaining. Cases with at least 10% of the tumor cells exhibiting nuclear p53 staining were considered positive 25…”
Section: Methodsmentioning
confidence: 99%